Digital government and meaningful connectivity: Opportunities and challenges for theory and practice - Ribiero, Manuella Maia; Cunha, Maria Alexandra; Estevez, Elsa; Gil-Garcia, J. Ramon (Conference on Digital Government Research, 2025)
The panel aims to explore the role of meaningful connectivity in digital government theory and practice, identify existing gaps, and propose future research directions. The meaningful connectivity perspective, which transcends binary Internet access metrics, is generally defined by the presence of infrastructure, affordability, and digital skills—dimensions considered crucial for ensuring that low-income and vulnerable populations can effectively use digital public services. The panel discussion will also showcase practical case studies of meaningful connectivity measurement in Brazil, Chile, the Dominican Republic, and Uruguay using the methodology developed by the Regional Center for Studies on the Development of the Information Society (Cetic.br), a UNESCO Category II center located in Brazil. By engaging experts and researchers in digital government, the panel intends to provide valuable insights for academics, policymakers, and practitioners aiming to enhance the adoption of digital public services and bridge digital divides.